Hydrothermal carbonization as a sustainable strategy for integral valorisation of apple waste. (August 2020) - Suárez, Loreto; Benavente-Ferraces, Iria; Plaza, César; de Pascual-Teresa, Sonia; Suárez-Ruiz, Isabel; Centeno, Teresa A.
Graphical abstract: Highlights: Integral and profitable management of apple waste by hydrothermal carbonization. Optical microscopy to evaluate successfully the transformation of biomass by HTC. Solid by-products are CO2 neutral fuels and show potential to enhance soil quality. Liquid by-products contain valuable phenolic compounds and saturated fatty acids. By-products properties are suited to final applications by selecting HTC conditions. Abstract: Hydrothermal carbonization makes feasible the integral and profitable recovery of industrial apple waste within a zero-residue bio-economy. 82–96% of the energy and 80–93% of the C in the apple bagasse are retained in the solids generated by hydrothermal treatment at 180 and 230 °C for 2 and 4 h. Such processes stabilize the apple waste and lead to CO2 neutral solid fuels with calorific value close to 30 MJ/kg. The agrochemical properties of the solid by-products suggest their potential to improve soil quality. Aqueous streams containing valuable phenolic compounds and saturated fatty acids are generated simultaneously, which provide additional cost-effectiveness. The by-products characteristics can be suited to the final application by selecting the reaction temperature, whereas the process duration has less impact. Optical microscopy and reflectance measurements are presented, for the first time, as powerful tools for assessing the biomass transformation when subjected to hydrothermal treatment under different conditions.